T cell related osteoimmunology in fracture healing: Potential targets for augmenting bone regeneration - Haixing Wang; Yashi Li; Haoxin Li; Xu Yan; Zhaowei Jiang; Lu Feng; Wenhui Hu; Yinuo Fan; Sien Lin; Gang Li (Journal of Orthopaedic Translation)
Last decade has witnessed increasing evidence which highlights the roles of immune cells in bone regeneration. Numerous immune cell types, including macrophages, T cells, and neutrophils are involved in fracture healing by orchestrating a series of events that modulate bone formation and remodeling. In this review, the role of T cell immunity in fracture healing has been summarized, and the modulatory effects of T cell immunity in inflammation, bone formation and remodeling have been highlighted. The review also summarizes the specific roles of different T cell subsets, including CD4+ T cells, CD8+ T cells, regulatory T cells, T helper 17 cells, and γδ T cells in modulating fracture healing. The current therapeutics targeting T cell immunity to enhance fracture healing have also been reviewed, aiming to provide insights from a translational standpoint. Overall, this work discusses recent advances and challenges in the interdisciplinary research field of T cell related osteoimmunology and its implications in fracture healing. The translational potential of this article: Delayed unions or non-unions of bone fractures remain a challenge in clinical practice. Developing a deep understanding of the roles of immune cells, including T cells, in fracture healing will facilitate the advancement of novel therapeutics of fracture nonunion. This review summarizes the current understanding of different T cell subsets involved in various phases of fracture healing, providing insights for targeting T cells as an alternative strategy to enhance bone regeneration.